2020
DOI: 10.1007/s11947-020-02510-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Thermal Treatments Applied to Meat Using Traditional Methods and Spectroscopic Techniques: a Review of Advances over the Last Decade

Abstract: Thermal treatments are often applied during processing or preparation of muscle foods aiming to both improve the palatability and organoleptic properties and to ensure the safety of the treated food. However, the application of inappropriate or severe thermal treatments can lead to undesirable changes in the sensory and nutritional quality of heat-processed products, and especially so for foods that are sensitive to thermal treatments, such as meat and meat products. The impact of traditional and new heat proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The sensory properties (i.e., appearance, aroma, flavor, taste, and texture attributes) of meat have long been recognized as an important factor for consumer acceptability (Boleman et al., 1997; Miller, 2017). Various traditional and novel cooking treatments, as well as their effects on meat physicochemical and sensory properties, have been investigated (Hassoun, Aït‐Kaddour, et al., 2020; Roldan et al., 2014; Troy et al., 2016). In addition, numerous studies have investigated how the physicochemical and sensory properties of meat are influenced by increasing end‐point cooking temperatures (i.e., increasing degrees of doneness) (Drey et al., 2019; George‐Evins et al., 2004; Schmidt et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sensory properties (i.e., appearance, aroma, flavor, taste, and texture attributes) of meat have long been recognized as an important factor for consumer acceptability (Boleman et al., 1997; Miller, 2017). Various traditional and novel cooking treatments, as well as their effects on meat physicochemical and sensory properties, have been investigated (Hassoun, Aït‐Kaddour, et al., 2020; Roldan et al., 2014; Troy et al., 2016). In addition, numerous studies have investigated how the physicochemical and sensory properties of meat are influenced by increasing end‐point cooking temperatures (i.e., increasing degrees of doneness) (Drey et al., 2019; George‐Evins et al., 2004; Schmidt et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ohmic heating, dielectric heating (i.e., radio frequency and microwave heating), and infrared heating are promising alternatives to conventional methods of heat processing. These novel thermal technologies are viewed as volumetric heating (internal heating) whereas conventional heating methods are based on convection and conduction (external heating) [66,67].…”
Section: Thermal Processingmentioning
confidence: 99%
“…Another study investigated the impact of microwave heating on the gel characteristics of surimi, and the results indicated that thickness of the surimi was the most important factor that influences the temperature distribution during microwave heating [78]. However, the cost of the equipment hinders its wider deployment at large-scale facilities [66,79].…”
Section: Thermal Processingmentioning
confidence: 99%
“…While the myofibrillar proteins from beef and lamb exhibited denaturation peaks of 55–60°C (Kemp, North, & Leath, 2009), the myosin and α‐actinin begin to denature from 40–50°C (Wright & Wilding, 1984; Cheng & Parrish, 1979), titin from 60°C (Pospiech et al., 2002) and actin from 70°C (Wright et al., 1977). SDS‐PAGE analysis showed denaturation of myosin and actin in the range of 60–80°C (Hassoun, Aït‐Kaddour, Sahar, & Cozzolino, 2021). No distinctive denaturation peaks were exhibited by the sarcoplasmic proteins of beef, lamb, or pork (Kemp et al., 2009), however, the maximum heat capacity values suggested that denaturation occurred between 50 and 70°C.…”
Section: Introductionmentioning
confidence: 99%